2014
DOI: 10.1080/01490400.2014.888022
|View full text |Cite
|
Sign up to set email alerts
|

Human Responses to Simulated Motorized Noise in National Parks

Abstract: HUMAN RESPONSES TO SIMULATED MOTORIZED NOISE IN NATIONAL PARKSThis thesis investigated the effects of three sources of motorized noise on laboratory participants' evaluations of landscape scenes, self-reported affective states, and physiological responses in simulated national park settings. Seventy-seven laboratory participants completed landscape assessments along 8 aesthetic dimensions and reported affective states while listening to audio clips of natural sounds, propeller planes, motorcycles, and snowmobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 44 publications
1
21
0
2
Order By: Relevance
“…In a later expended study, Benfield et al (2010) showed that aircraft and road traffic noise decreased ratings in scenic evaluation of natural landscape especially for scenes of high scenic beauty. Using similar landscape evaluation procedure and aesthetic indicators, Weinzimmer et al (2014) investigated the effect of noises of propeller planes, motorcycles, and snowmobiles in national parks. The results indicated that all the three motorised noises detracted from the evaluation of landscape quality and the motorcycle noise had the most detrimental impact.…”
Section: Introductionmentioning
confidence: 99%
“…In a later expended study, Benfield et al (2010) showed that aircraft and road traffic noise decreased ratings in scenic evaluation of natural landscape especially for scenes of high scenic beauty. Using similar landscape evaluation procedure and aesthetic indicators, Weinzimmer et al (2014) investigated the effect of noises of propeller planes, motorcycles, and snowmobiles in national parks. The results indicated that all the three motorised noises detracted from the evaluation of landscape quality and the motorcycle noise had the most detrimental impact.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has consistently demonstrated a deleterious effect of anthropogenic noise on scenic evaluations and affect (e.g., Mace et al, 1999; Weinzimmer et al, 2014), but the examination of moderating variables within this type of soundscape assessment has been limited to situational characteristics such as the cause (Mace et al, 2003) or location (Benfield et al, 2010) of the noise. The current study demonstrated that the individual-level characteristics of attitudes toward motorized recreation noise and soundscape management can also affect the severity of anthropogenic noise-related outcomes in simulated natural recreation environments.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Weinzimmer et al (2014) further refined the assessment of specific soundscape events by comparing directly three common sources of motorized noise in national parks – motorcycles, propeller planes, and snowmobiles. Using a carefully controlled laboratory simulation, Weinzimmer et al (2014) directly compared different motorized vehicle soundscapes using a within-subjects design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While research conducted on motorcycling is available, it covers a wide range of topics, for example the ethnographic aspects (Conner 2009;Levingston & Zimmerman 2003;Schouten & McAlexander 1995), environmental aspects (Leong, Muttamara & Laortanakul 2002), safety (Elliott et al 2003;Weinzimmer et al 2014), cultural significance (Maynard 2008;Packer & Coffey 2004), charity runs (Rabinowitz 2007), adventure motorcycling (Price-Davies 2011), spirituality (Litton 2008), spending analysis (Kruger, Viljoen & Saayman 2015) and motivation (Garber 2002;Hagen, Pardo & Valente 2016;Kruger et al 2014;Thompson & Thompson 2014). Authors of studies on gender aspects of motorcycling include Cockburn and Ormond (1993); Hopper and Moore (1990); Kelkar and Nathan (2002) ;Martin, Schouten and McAlexander (2006);Mellström (2004);Meyer (2009) ;Oyesiku and Odufuwa (2002);Roster (2007); Thompson (2012);and Veno and Winterhalder (2009).…”
Section: Literature Reviewmentioning
confidence: 99%